2020
DOI: 10.3390/ijerph17207356
|View full text |Cite
|
Sign up to set email alerts
|

Gingival Crevicular Blood as a Potential Screening Tool: A Cross Sectional Comparative Study

Abstract: Background: Diabetes is known to be one of the major global epidemic diseases, significantly associated with mortality and morbidity worldwide, conferring a substantial burden to the health care system. The epidemiological transition of this chronic disease tends to worsen unless preventive health strategies are implemented. Appropriate screening devices and standardized methods are crucial to prevent this potentially inauspicious life condition. Currently, the glucometer is the conventional device employed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 29 publications
1
18
1
Order By: Relevance
“…The treatment of a patient with diabetes requires consideration of key pathogenic characteristics, the duration of disease, the age of patient and the presence of secondary diagnoses for specific complications or comorbidities [ 38 ]. Priority in management diabetes is the regression of pathology, by reaching the euglycemia and controlling the metabolic alterations [ 5 , 39 , 40 , 41 , 42 ]. The role of inflammation is under intensive scrutiny with several clinical trials to have been completed while more are in development [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of a patient with diabetes requires consideration of key pathogenic characteristics, the duration of disease, the age of patient and the presence of secondary diagnoses for specific complications or comorbidities [ 38 ]. Priority in management diabetes is the regression of pathology, by reaching the euglycemia and controlling the metabolic alterations [ 5 , 39 , 40 , 41 , 42 ]. The role of inflammation is under intensive scrutiny with several clinical trials to have been completed while more are in development [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study glucometer was used as a chairside diagnostic device, for RBS evaluation,[ 37 ] in order to improve the patient's comfort. As the literature also mentions that in some cases, HbA1c cannot be trusted due to defect in glycation or severe anemia.…”
Section: Discussionmentioning
confidence: 99%
“…Random blood sugar (RBS) level was evaluated at baseline and 8 weeks after treatment, using glucometer, by capillary finger-prick method. [ 36 37 ]…”
Section: Methodsmentioning
confidence: 99%
“…The present finding revealed that the serum level of MDA was significantly increased in the experimental induced diabetes and periodontitis untreated group (EDP) as compared to the control group for all duration periods of 0, 7, 14, and 21 days. This increase may have been due to the fact that periodontitis was in active state and the peripheral blood neutrophils exhibited a hyperactive phenotype in terms of the production of ROS, which may have diffused into the blood stream [ 7 , 25 ]. This result was supported by a study on experimentally induced periodontitis in hyperglycemic Wistar rats [ 14 ] and demonstrated a significant elevation of MDA serum level in the untreated EDP group as compared to the control group.…”
Section: Discussionmentioning
confidence: 99%